2015
DOI: 10.1016/j.schres.2014.09.045
|View full text |Cite
|
Sign up to set email alerts
|

White matter diffusivity and microarchitecture among schizophrenia subjects and first-degree relatives

Abstract: Background Impairments in structural and functional connections are demonstrated in schizophrenia. Certain disconnectional patterns may be biomarkers of elevated risk for schizophrenia. Convergent examination of multiple diffusion parameters and cognitive performance better illustrates pathophysiological significance of such disconnectional patterns. Methods Diffusion Tensor Imaging data on 39 early-course schizophrenia subjects, 21 adolescent/young adult first-degree relatives (FDR) of schizophrenia subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…This study allowed non-psychotic psychiatric disorders in the relative group. Another recent study using TBSS also found decreased FA in forceps minor and decreased RD in the SLF and forceps minor in relatives compared to control (Prasad et al, 2014). …”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…This study allowed non-psychotic psychiatric disorders in the relative group. Another recent study using TBSS also found decreased FA in forceps minor and decreased RD in the SLF and forceps minor in relatives compared to control (Prasad et al, 2014). …”
Section: Resultsmentioning
confidence: 77%
“…All but two of the fourteen studies found some abnormalities in the relative group compared to healthy controls (Boos et al, 2013; Camchong et al, 2009; Clark et al, 2011; Goghari et al, 2014; Hao et al, 2009; Hoptman et al, 2008; Knöchel et al, 2012a, 2012b; Muñoz Maniega et al, 2008; Phillips et al, 2011; Prasad et al, 2014; Skudlarski et al, 2013). Ten of these studies found decreased FA (Camchong et al, 2009; Clark et al, 2011; Hao et al, 2009; Hoptman et al, 2008; Knöchel et al, 2012a, 2012b; Muñoz Maniega et al, 2008; Phillips et al, 2011; Prasad et al, 2014; Skudlarski et al, 2013), four found increased FA (Boos et al, 2013; Goghari et al, 2014; Hoptman et al, 2008; Knöchel et al, 2012a), one found increased ADC (Knöchel et al, 2012b), and one found decreased RD (Prasad et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported connectivity issues between frontal and occipital cortices (Fornito et al, 2011;Liu et al, 2012;Cheng et al, 2015), including fractional anisotropy deficits of inferior and superior longitudinal fasciculus pathways (Lener et al, 2015;Prasad et al, 2015). Therefore, although from EEG recordings we can only indirectly infer the cortical sources underlying scalp recorded activity, the current findings of decreased alpha resonance in frontal regions may reflect resonance deficits particularly in the frontal cortex, perhaps mediated by thalamo-cortical abnormalities, in addition to dysfunction in connectivity between occipital and frontal cortices preventing alpha oscillations from reaching frontal regions.…”
Section: Potential Pathophysiological Mechanismsmentioning
confidence: 99%